PELATIHAN PERENCANAAN KEUANGAN BAGI SISWA SMA DI SEKOLAH GAJAH MADA MEDAN - Khairani, Khairani; Sitompul, Pretty Naomi; Salim, Denny; Winata, Clarrissa; Wijaya, Selvia Fransiska (Jurnal Pengabdian Bukit Pengharapan, 2024)
The Community Service Program (PKM) titled "Financial Planning Training for Students at Gajah Mada High School Medan" aims to enhance financial literacy among high school students through lectures, interactive discussions, and practical simulations. This program successfully improved students' understanding of basic financial planning concepts, such as budgeting, the importance of saving, and wise expenditure management. However, some students still faced challenges in distinguishing between needs and wants and allocating budgets effectively. Parental involvement was also identified as a critical factor in fostering good financial habits among students. Overall, this program made a positive contribution to increasing students' financial literacy and instilling financial management skills beneficial for their future. Recommendations include conducting follow-up training sessions and enhancing sustained parental involvement.